Group Resume Learning through Drama in Instructional Technology Course - Artina Diniaty; Lina Fauzi'ah (IJCER (International Journal of Chemistry Education Research), 2017)
ABSTRACT: The implementation of group resume learning through drama in instructional technology subjects aimed to create a pleasant atmosphere and improve student creativity in learning so as to facilitate them in understanding the material being studied. The implementation of the research was conducted in four stages: plan, implementation, observation, and evaluation. The results showed that 1) the assessment of drama on group resume learning through drama in instructional technology course is very good, and 2) student response to group resume learning through drama in instructional technology course is very good.Keywords: group resume, drama, instructional technologyReceived: 10 June 2017, Revised: 5 August 2017, Accepted: 1 September 2017